The complete mitochondrial genome of the Montipora peltiformi (Scleractinia: Acroporidae) - Xin Wang; Peng Tian; Wentao Niu; Shuangen Yu (Mitochondrial DNA. Part B. Resources, 2018)
In this study, the complete mitogenome sequence of stony coral, Montipora peltiformi (Scleractinia), has been decoded for the first time by next generation sequencing and genome assembly. The assembled mitogenome, consisting of 17,884 bp, has unique 13 protein coding genes (PCGs), three transfer RNAs, and two ribosomal RNAs genes. The complete mitogenome of Montipora peltiformi showing 99% identities to Montipora cactus. The complete mitogenome provides essential and important DNA molecular data for further phylogenetic and evolutionary analysis for coral phylogeny.